2010
DOI: 10.3174/ajnr.a2280
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Correlation of Tumor Blood Volume and Permeability with Histologic and Molecular Angiogenic Markers in Gliomas

Abstract: BACKGROUND AND PURPOSE:Tumor angiogenesis is very heterogeneous and in vivo correlation of perfusion imaging parameters with angiogenic markers can help in better understanding the role of perfusion imaging as an imaging biomarker. The purpose of this study was to correlate PCT parameters such as CBV and PS with histologic and molecular angiogenic markers in gliomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 31 publications
4
77
1
2
Order By: Relevance
“…PCT has also been reported to differentiate grade III from grade IV gliomas with PS demonstrating better predictability than BV in this regard (C-statistic = 0.926 and 0.787, respectively) [17]. This is consistent with the correlation between PS and MVCP [11] in that neovascularization is a criterion for diagnosing grade IV gliomas, but not grade III gliomas, suggesting PS is sensitive to detecting immature and leaky tumor vessels. In addition to grading, PS has been shown to improve interobserver agreement of tumor boundary delineation, which is particularly important for tumor targeting by radiotherapy [23].…”
Section: Correlation With Histopathologic Markers and Tumor Gradesupporting
confidence: 74%
See 2 more Smart Citations
“…PCT has also been reported to differentiate grade III from grade IV gliomas with PS demonstrating better predictability than BV in this regard (C-statistic = 0.926 and 0.787, respectively) [17]. This is consistent with the correlation between PS and MVCP [11] in that neovascularization is a criterion for diagnosing grade IV gliomas, but not grade III gliomas, suggesting PS is sensitive to detecting immature and leaky tumor vessels. In addition to grading, PS has been shown to improve interobserver agreement of tumor boundary delineation, which is particularly important for tumor targeting by radiotherapy [23].…”
Section: Correlation With Histopathologic Markers and Tumor Gradesupporting
confidence: 74%
“…PCT measures of BF and BV have shown significant correlations with MVD (r = 0.527 and 0.649, respectively; P < 0.02), while PS showed a significant correlation with MVCP (r = 0.647, P = 0.001) [11]. These results suggest that regions of higher angiogenic activities (i.e.…”
Section: Correlation With Histopathologic Markers and Tumor Gradesupporting
confidence: 56%
See 1 more Smart Citation
“…This result is not surprising given evidence that CBV or CBF measures or both have been seen in other recent (largely retrospective) studies to correlate with tumor grade and, in high-grade glial tumors, with cellular proliferation, response to treatment, and time to progression. 12,13,26,27,29,30,32,[39][40][41][42] In the current study, not only was the experts' confidence significantly affected by the addition of the perfusion imaging, but the management plan was actually changed in 5 of the 59 patient episodes of care (8.5%). Although this was not a diagnosticaccuracy study, we subsequently retrospectively reviewed these patients' medical records and found that the changes suggested by the perfusion imaging interpretations seemed to have aligned with the subsequent behavior of their tumors in 4 patients (1 patient's subsequent tumor behavior could not be determined).…”
Section: Discussionmentioning
confidence: 86%
“…These findings suggest that these 2 perfusion parameters represent different aspects of tumor angiogenesis and in vivo identification, which could be of clinical importance. 26 Better understanding of the histologic basis for these hemodynamic and physiologic parameters could help increase their use as imaging biomarkers.…”
Section: Heterogeneity Of Glioma Angiogenesis and Perfusion Imagingmentioning
confidence: 99%